Disponibilidade de recursos florais oferecidos por três espécies de Malpighiaceae em um cerrado no sudeste brasileiro: a relação com seus visitantes florais - Barônio, Gudryan Jackson (2013)
Eleven botanical families provide floral oil, one of these is Malpighiaceae. This family is well known for its varied biological interactions, many of them are due to the oil-producing glands called elaiophores, located at the base of the sepals. Besides the oil, flowers also offer pollen and both are usually found in nests of large bees. Thus, this family is essential for the maintenance and survival of the guild of floral oil collecting bees in the Neotropical region. Considering the ecological importance of Malpighiaceae, given its close links with oil collecting bees, and considering that the carrying capacity of such plants can provide a measure of habitat quality for these bees, we decided to investigate the importance of floral resources for these interactions and observed the similarities in the bee fauna in each species. For this study we selected three abundant species in a savanna reserve in southeastern Brazil, Banisteriopsis campestris, B. malifolia and Peixotoa tomentosa. Flower visitors and their behavior were recorded and, in addition, the quantification and qualification of floral oil and the quantification of pollen were investigated. The resource availability varies both qualitatively and quantitatively between species. We recorded 31 visitors species with different behavior among them and also between the Malpighiaceae species, demonstrating that more effective pollination is caused by larger bees as a consequence of proper behavior and visitation time. Differences in the composition of floral visitors between plant species indicate seasonal variation in bee fauna, considering that the flowering of three species had partial overlap. The major species overlaps occur between visitors of B. campestris and B. malifolia and between B. malifolia and P. tomentosa. Differences in quantity and quality of floral oil between species are proposed as an explanation for the diverse attractiveness and/or lack of specificity of oil-collecting bees, where there are many bees species collecting the resources.